Petroleum hydrocarbon degradation by isolated mangrove bacteria - Lustosa, Mayara A. (2018)
The petroleum hydrocarbon contamination represents a worldwide problem, since its accumulation promotes a serious environmental impact. Thereby, the use of microorganisms, such as those from mangrove micro biota, as degrading agents of various carbon sources is poorly exploited in environmental remediation processes. Thus, this in vitro study evaluated the degrading potential of isolated bacteria from mangrove sediments in the degradation of petroleum hydrocarbons. Analysis of the genetic diversity using the 16S rRNA marker revealed closely related (99%) sequences with Proteobacterium, Pseudomonas and Exiguobacterium. Results showed the bacterial growth in the mineral saline medium (MSM) containing 1% petroleum or diesel, as carbon sources. This growth was determinated by optical density at 595 nm for 15 days, with sample withdrawal every 48 h. Bacterial growth indicated the hydrocarbon metabolization. However, bacteria were more efficient at degrading petroleum. Overall, experimental data displayed the potential application of these bacteria in bioremediation processes, due to their metabolic and adaptive capacities to grow in a rich hydrocarbon medium.